2021
DOI: 10.1080/22054952.2021.1913882
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning ethics at the heart of engineering graduate attributes

Abstract: The integration of ethics in engineering education has largely been focused at the curriculum design level. The authors posit that this integration be done at the accreditation level and investigate how ethics may be more extensively incorporated in the documentation of a particular engineering accreditation body's qualification standards. The paper proceeds, by means of a narrative review, to justify an expanded conception of the teaching of ethics within engineering education. It builds a synthesis of contra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A survey of engineering ethics educators at two South African universities also revealed that whilst ethics education was viewed as important, ethics educators had different understandings of what should be covered in ethics courses [10]. Few of the engineering programmes explicitly highlighted ethics in learning outcomes or assessment procedures, and educators felt that they did not have the skills to teach the subject.…”
Section: South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of engineering ethics educators at two South African universities also revealed that whilst ethics education was viewed as important, ethics educators had different understandings of what should be covered in ethics courses [10]. Few of the engineering programmes explicitly highlighted ethics in learning outcomes or assessment procedures, and educators felt that they did not have the skills to teach the subject.…”
Section: South Africamentioning
confidence: 99%
“…The authors of the study subsequently suggested that engineering ethics educators needed more support to master their subject. In another study, the same authors also advocated the repositioning of ethics within the engineering curriculum as a transdisciplinary area that provides context and rationale for the selection and 50th Annual Conference in September 2022 2105 practice of technical skills and knowledge developed in the discipline [11]. The authors suggest that such an approach will help to bring ethics from the periphery of curriculum design consideration to a position where ethics is viewed as the basis by which engineers make the necessary technical, mechanical and process choices in pursuance of their professional and ethical responsibilities and obligations.…”
Section: South Africamentioning
confidence: 99%
“…What negative consequences can result on the engineering profession if data collection and communication is not been completed ethically? As is implied by Gwynne-Evans, Chetty[11], does ethics need repositioning?…”
mentioning
confidence: 99%